Health Care Providers’ Readiness to Screen for Intimate Partner Violence in Northern Nigeria - John, I. A.; Lawoko, Stephen; Svanström, L.; Mohammed, A. Z. (Violence and Victims, 2010)
Research on screening for intimate partner violence (IPV) within health care in a sub- Saharan African context is rare. This paper assessed factors associated with the readiness to screen for IPV among care providers (HCP, n = 274) at Kano hospital, Nigeria. Readiness was measured using the Domestic Violence Health Care Providers’ survey instrument, which measures grade of perceived self-effi cacy in screening for IPV, fear for victim/provider safety, access to system support to refer IPV victims, professional roles resistant/ fear of offending clients, and blaming the victim for being abused victim. Social workers perceived a higher self-effi cacy and better access to system support networks to refer victims than peers in other occupation categories. Female care providers and doctors were less likely to blame the victim than males and social workers, respectively. Younger care providers of Yoruba ethnicity and social workers were less likely to perceive confl icting professional roles related to screening than older providers of Hausa ethnicity and doctors, respectively. Implications of our fi ndings for interventions and further research are discussed.
Keywords: Health care providers; Intimate partner violence; Screening; Nigeria